A comparative numerical analysis of design variation plans for a shallow tunnel in very soft ground after a sudden accident. (November 2022) - Zhang, Zixin; Li, Jiayu; Wang, Shuaifeng; Huang, Xin
Highlights: A comparative numerical analysis of tunnel support variation plans is conducted. The evaluation factors are stress distribution, ground deformation and soil arching. The advance core's stability is crucial for preventing the excavation face failure. The support design of soil reinforcement via sub-horizontal MJS piles is recommended. The effectiveness of soil reinforcement by MJS piles is verified by field data. Abstract: A severe accident of surrounding soil failure occurred during the construction of Zizhi Tunnel, a shallow tunnel in very soft ground using the shallow tunneling method in Hangzhou, China. We provide an in-depth comparison with careful evaluation of three design variation plans through 3D numerical analyses on the stress distribution inside the advance core, ground deformation, and soil arching over the tunnel crown. Consequently, the third support design scheme, i.e., soil reinforcement using sub-horizontal Metro Jet System (MJS) piles, is recommended as it leads to the smallest disturbance to the surrounding ground, and is the most favorable for the soil arching formation. We also find that the advance core's stability is crucial for preventing the face failure and reducing the surface settlement. Finally, the effectiveness of world's first successful example of applying sub-horizontal MJS piles to reinforce tunnel excavation in very soft soil is verified by the field monitoring data.